The Psychological Impact of Fatherless on Women: A Systematic Literature Review - Aurellia Dyahakta Putri; Iswinarti Iswinarti; Yuni Nurhamida (Interdisciplinary Social Studies, 2026)
Fatherlessness, defined as the absence of a father due to death, divorce, or psychological non-involvement, has increasing relevance in Indonesia. The study aims to systematically review literature to identify and categorize the psychological impacts of fatherlessness on women, examining differences based on the form of fatherlessness experienced. A systematic literature review was conducted using SCOPUS and Publish or Perish 8.1, following PCC (Population, Concept, Context) scoping questions. Inclusion criteria: qualitative studies (2020–2025) on women, published in English or Indonesian, focusing on psychological impacts of fatherlessness. From 212 journals, 14 met all criteria (see PRISMA chart, page 3). Five major psychological impact categories were identified: (1) interpersonal and sexual relationship problems, (2) low self-concept and identity issues, (3) negative emotions and mental health disorders, (4) social withdrawal and difficulty expressing oneself, and (5) cognitive and performance issues (pages 4–7). Variations in impact were noted depending on fatherlessness type: divorce, death, psychological absence, and domestic violence, with domestic violence yielding the most severe outcomes. Fatherlessness significantly affects women across multiple psychological dimensions. The impact varies by type of fatherlessness, influencing the intensity and complexity of emotional, social, and cognitive challenges.